EFEK EKSTRAK DAUN PIRDOT (Saurauia vulcani Korth) TERHADAP WAKTU EPITELISASI, KONTRAKSI LUKA DAN GAMBARAN HISTOLOGIS PADA PENYEMBUHAN LUKA EKSISI TIKUS PUTIH GALUR SPRAGUE DAWLEY - Patricia Oktaviani (2014)
Wound is disruption of the continuity of the tissues produced by external force. There are many factors that affect the speed of wound healing process. Medicinal drugs, irrigation with physiological NaCl 0,9% solution, and traditional drugs given are some of the ways that can accelerate the process. Pirdot (Saurauia vulcani Korth) has been used by tribe in North Sumatra as traditional medicine to heal wounds. This research is aim to study the effects of pirdot (Saurauia vulcani Korth.) leaves to wound contraction, reepithelization time, and histological appearance, in albino Sprague Dawley rat excised wound healing process. The research is a experimental study using albino rat with post-test only controlled group design. In this reasearch 25 albino rats were divided in 5 groups that given 40% extract concentration, 20% extract concentration, and 10% extract concentration, with one positive control using NaCl 0,9%, and one negative control. Circular wound excision were made by punch biopsy on right side and left side of rats backside, the wound were observed until the reepithelization progress were completed, and in day 10 one of the wound were taken to processed as the histological slide. Datas were analyzed using ANNOVA. Accuired that ethanolic extract of pirdot (Saurauia vulcani Korth.) accelerated the reepithelization time by day 14, pirdot (Saurauia vulcani Korth.) extract with 40% concentration is the most effective to speed wound contraction and also tissue maturation on histological appearance on day 10. Continous research with serial study of histological appearance is needed to know extract effect in the wound healing phases.